2021
DOI: 10.1002/cam4.3868
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meningioma surgery on use of antiepileptic, antidepressant, and sedative drugs: A Swedish nationwide matched cohort study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, we did not account for preoperative seizures in the analyses and with longer follow-ups frequencies of seizures would be expected to increase. In a Swedish registry-based study, nearly one in five meningioma patients were still on antiepileptic drugs 2 years after surgery [ 30 ]. Thus, due to the frequent use of antiepileptic drugs postoperatively in patients with preoperative seizures, and due to the short follow-up in many studies, underestimation of postoperative seizure frequencies is likely.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not account for preoperative seizures in the analyses and with longer follow-ups frequencies of seizures would be expected to increase. In a Swedish registry-based study, nearly one in five meningioma patients were still on antiepileptic drugs 2 years after surgery [ 30 ]. Thus, due to the frequent use of antiepileptic drugs postoperatively in patients with preoperative seizures, and due to the short follow-up in many studies, underestimation of postoperative seizure frequencies is likely.…”
Section: Discussionmentioning
confidence: 99%
“…The low levels of antidepressant use in VS patients are interesting considering what is known for low-grade glioma [ 33 ] and meningioma [ 43 ], where the rate of antidepressant use is distinctly increased after surgery. For low-grade glioma, the increased use of antidepressants is presumably related to the higher morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Our study of a comparable population undergoing meningioma surgery during a similar time period demonstrated a clear peak around the time of surgery and a slight increase in long-term sedative use [ 43 ]. The expected brief, but significant, increase in sedative use for patients a few weeks after the index date did not cause long-term increased use in patients with VS.…”
Section: Discussionmentioning
confidence: 99%
“…frontal convexity, falx or olfactory groove meningiomas). Depressive symptoms and fatigue are common amongst all meningioma patients 53–55 ; thus, these symptoms cannot only be caused by direct, local tumour pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring quality of life and everyday life from a patient perspective in patients with WHO grade 3 meningioma are non‐existing. In meningioma, irrespective of grade, recent studies found a long‐term reduction in health‐related quality of life, 103,104 elevated use of anti‐depressants even two years after surgery, 54 and a high burden of socioeconomic difficulties after meningioma surgery 105 . Moreover, patients with meningioma experienced a lack of support in the postoperative phase for optimal recovery 106 and could experience a paradox when they had to undergo extensive surgery for a benign tumour 107 .…”
Section: Introductionmentioning
confidence: 99%